Timeliness Of Financial Reporting: Financial Performance With Audit Opinion Evidence Indonesia - Juninetenth Keeply F Sitanggang; Viola Syukrina E Janrosl; Ronald Wangdra; Handra Tipa (LPPM Universitas Putera Batam, 2026)
Financial statements presented on time provide transparency into the company's financial condition. Financial statements offered on time can increase the trust and credibility of the company. This study uses audit opinion as a moderating variable to analyze and describe the effect of solvency, liquidity, and profitability on the timeliness of financial reporting. The problem in this study is that there are still going public companies that are still required to report their financial statements on time. In 2021, 32 companies are still required to submit financial statements. Some companies need to be audited and reviewed more. Meanwhile, as many as 699 companies have reported financial statements on time. This research is quantitative research using secondary data. The population in this study is cement companies listed on the Indonesia Stock Exchange in 2019-2023. The sampling technique uses purposive sampling. Analysis techniques with the SEM-PLS approach are processed with SMART PLS. The results showed that liquidity, audit opinion, and profitability variables did not significantly affect the timeliness of financial reporting. The solvency variable has a significant effect on the timeliness of financial reporting. Audit opinion was not able to be a moderation variable in this study. This is because audit opinions focus more on assessing the quality of financial information, such as the accuracy, adequacy, and disclosure of information presented in financial statements.